Implementasi Diversi dalam Penyelesaian Perkara Pidana Pengeroyokan: (Studi Kasus Kejaksaan Negeri Jombang) - Muhammad Widjayanto (CV Rewang Rencang, 2025)
Diversion is mandatory for all law enforcement officials, including those at the prosecution stage. Implementing diversion in handling juvenile cases is a form of fulfilling children's rights. Currently, there have been 40 cases of assault perpetrated by juveniles at the Jombang District Attorney's Office over the past three years. However, only one case has been successfully diverted. One of the cases successfully diverted is registered as PDM./89/M.5.25/VI/2024. The Jombang District Attorney's Office has struggled to achieve diversion due to several obstacles, including limited time, difficulty in bringing the parties together, and the victim's reluctance to pursue diversion.